2005
DOI: 10.1194/jlr.m500112-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

CD36 deficiency in mice impairs lipoprotein lipase-mediated triglyceride clearance

Abstract: CD36 is involved in high-affinity peripheral FFA uptake. CD36-deficient ( cd36 ؊ / ؊ ) mice exhibit increased plasma FFA and triglyceride (TG) levels. The aim of the present study was to elucidate the cause of the increased plasma TG levels in cd36 ؊ / ؊ mice. cd36 ؊ / ؊ mice showed no differences in hepatic VLDL-TG production or intestinal [ 3 H]TG uptake compared with wild-type littermates. cd36 ؊ / ؊ mice showed a 2-fold enhanced postprandial TG response upon an intragastric fat load ( P Ͻ 0.05), with a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
66
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 30 publications
9
66
2
Order By: Relevance
“…Our studies, however, do not agree well with those of Goudriaan et al 23,31 Using an inhibitor of intravascular lipolysis, Triton WR1339, they showed that CD36 KO and WT mice were comparable in the plasma recovery of infused TG and FA. We cannot explain the discrepancy between their findings and ours, but it should be noted that their plasma TG recovery was only about 15% of the total infused by the end of 4 hours as compared with our lymphatic recoveries of about 44% of the total infused for WT and 18% for the KO animals.…”
Section: Discussioncontrasting
confidence: 99%
“…Our studies, however, do not agree well with those of Goudriaan et al 23,31 Using an inhibitor of intravascular lipolysis, Triton WR1339, they showed that CD36 KO and WT mice were comparable in the plasma recovery of infused TG and FA. We cannot explain the discrepancy between their findings and ours, but it should be noted that their plasma TG recovery was only about 15% of the total infused by the end of 4 hours as compared with our lymphatic recoveries of about 44% of the total infused for WT and 18% for the KO animals.…”
Section: Discussioncontrasting
confidence: 99%
“…Correlation analysis revealed that CD36 was positively correlated with LDL, which is similar to the findings of previous studies (Yamashita et al, 2007;Xie et al, 2011;Babaahmadi Rezaei et al, 2013). Goudriaan et al (2005) observed an increase in TG levels in CD36 knockout mice, similar to the results of the present study. These findings indicate that lipoprotein is regulated by the level of CD36 gene and protein expression, which subsequently affects cellular cholesterol levels.…”
Section: Discussionsupporting
confidence: 81%
“…Moreover, it has been reported that CD36 plays a role in plasma TG homeostasis via modulation of LPL activity (Goudriaan et al, 2005). Thus, an increase of this gene expression would be one of the mechanisms of plasma TG level decrease in the corresponding animal.…”
Section: Discussionmentioning
confidence: 99%